Partial femoral head replacement: a new innovative surgical technique for precise minimally invasive treatment of association research circulation osseous stage III femoral head necrosis - Tianyu Wang; Zhongzheng Wang; Yuchuan Wang; Changhui Li; Yining Lu; Yanbin Zhu; Wei Chen; Xuebin Zhang; Yingze Zhang (BMC Musculoskeletal Disorders)
Abstract Background Association Research Circulation Osseous (ARCO) stage III is the last chance for joint preservation in patients with osteonecrosis of the femoral head (ONFH). As the femoral head has collapsed at this stage, existing hip-preserving surgical treatments show limited success. We aimed to introduce a new surgical technique called partial femoral head replacement for the treatment of ARCO III femoral head necrosis and to evaluate its safety and efficacy. Methods Between November 2022 and December 2022, 11 symptomatic hips from 11 patients were enrolled in this retrospective study. The surgeon precisely removed the necrotic area of the femoral head through a bone tunnel at the femoral neck and implanted a prosthesis that matched each patient’s anatomy and femoral head contour. Details of the demographics, surgical information, imaging findings, and any complications were retrospectively collected. Clinical scores, including the visual analogue scale (VAS) score, Harris Hip Score (HHS), and 12-Item Short-Form Health Survey (SF-12) scores, were determined. Each patient was followed for at least one year. Results The mean operative time per hip was 57.27 ± 15.23 min, the mean estimated blood loss was 110 ± 60.62 ml, and the mean incision length was 3.35 ± 0.38 cm. The VAS score at the one-year follow-up showed great pain relief (7.5 ± 0.9 vs. 1.6 ± 1.2, P < 0.01). The HHS improved significantly compared to the preoperative score (90.3 ± 3.7 vs. 42.9 ± 4.4, P < 0.01). The SF-12 scores also showed that all patients experienced varying degrees of physical (42.1 ± 5.1 vs. 27.7 ± 7.1, P<0.01) and mental (44.3 ± 4.7 vs. 36.4 ± 3.8, P<0.01) health improvement. Radiologically, there were no abnormalities on the latest imaging examination. Clinically, no serious postoperative complications occurred during the treatment. Conclusions Our preliminary clinical results showed that partial femoral head replacement was a safe and effective method for the treatment of ARCO III femoral head necrosis. With the trend of younger ONFH patients and increasing emphasis on hip preservation, partial femoral head replacement may provide a new minimally invasive hip-preserving option for these patients.